1981
DOI: 10.1038/bjc.1981.46
|View full text |Cite
|
Sign up to set email alerts
|

In vitro demonstration of in situ autologous tumour-cell cytotoxicity in MSV-induced tumours in A/SN mice

Abstract: Summary.-Moloney sarcoma-virus (MSV)-induced tumours in A/Sn mice have been dispersed with collagenase and DNase 8-15 days after virus inoculation, and both "sarcoma" and inflammatory cells separated by sedimentation velocity and adherence techniques. The isolated "sarcoma" cells had the morphological characteristics of atypical cells (i.e. cytoplasmic blebbing, vacuolization and prominent nucleoli) and were easily adapted to in vitro growth. As few as 2 x 103 of these cells inoculated i.m. produced new tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…T cells are present neither in the spleen nor in the tumor (Becker and Haskill, 1980~). Regression therefore must depend on inflammatory processes regulated by T cells but not by their cytolytic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T cells are present neither in the spleen nor in the tumor (Becker and Haskill, 1980~). Regression therefore must depend on inflammatory processes regulated by T cells but not by their cytolytic effect.…”
Section: Discussionmentioning
confidence: 99%
“…These cells inhibited T-cell mitogen responses, antibody responses and proliferation of lymphoma cells. When the studies were extended to MSV-intratumoral mechanisms, macrophages were found with non-specifically cytostatic (Holden et al, 1976) and cytolytic (Puccetti and Holden, 1979) effects against in vitro tumor lines.In a series of experiments analyzing the nature of the morphologically atypical presumptive sarcoma cells isolated from MSV tumors, we found that these cells were highly virus-infected but not transformed (Becker and Haskill, 1980~). Thus it was of interest to investigate whether the granulocytes and macrophages, the two predominant inflammatory cell types present in these tumors, were active against the autochthonous virus-releasing cells responsible for propagation of the MSV lesion, In the first paper we investigated the cytolytic capacity of the granulocytes (Becker and Haskill, 19806).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Sera containing the highest titer of neutralizing antibodies are also the most effective in preventing M-MSV tumorigenesis, suggesting that neutralizing antibodies are probably responsible for this in vivo protection (LCvy and Leclerc, 1977). An alternative possibility emerges from studies by Becker and co-workers (Becker and Klein, 1980;Becker and Haskill, 1981), who were unable to demonstrate CTL in the N S n mouse during M-MSV tumor development and regression. They speculated that both cytotoxic granulocytes and macrophages, demonstrable in M-MSV tumors in this mouse strain, might play a role in regression of the tumor (Becker and Haskill, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility emerges from studies by Becker and co-workers (Becker and Klein, 1980;Becker and Haskill, 1981), who were unable to demonstrate CTL in the N S n mouse during M-MSV tumor development and regression. They speculated that both cytotoxic granulocytes and macrophages, demonstrable in M-MSV tumors in this mouse strain, might play a role in regression of the tumor (Becker and Haskill, 1981). However, it remains to be elucidated whether these effector cells alone are capable of causing tumor regression.…”
Section: Discussionmentioning
confidence: 99%